2019
DOI: 10.1002/ece3.4955
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Abies alba and Picea abies saplings to browsing and frost damage depends on seed source

Abstract: The density of wild ungulates has increased in the last century, and browsing has become a major driver of forest succession in the northern hemisphere. In addition, tree species are expected to respond differently to future climate conditions, especially an increased frequency of late frost events. The aim of this study was to analyze the influence of intraspecific genetic variation on the recovery of two tree species to frost and browsing. An experiment with saplings from 90 Abies alba and 72 Picea abies see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 30 publications
2
20
0
4
Order By: Relevance
“…Previous analysis of growth traits in the same common garden experiment showed that seedlings recovered from the stress caused by simulated ungulate browsing when only their terminal buds were browsed, but not after the removal of several shoots (i.e. heavy browsing) Kupferschmid & Heiri (2019). Here, we hypothesized that the e ect of simulated browsing on physiological traits related to C and N balance would be largely diminished.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Previous analysis of growth traits in the same common garden experiment showed that seedlings recovered from the stress caused by simulated ungulate browsing when only their terminal buds were browsed, but not after the removal of several shoots (i.e. heavy browsing) Kupferschmid & Heiri (2019). Here, we hypothesized that the e ect of simulated browsing on physiological traits related to C and N balance would be largely diminished.…”
Section: Introductionmentioning
confidence: 87%
“…1A and B). In March 2015, at the start of the third eld growing season, a simulated browsing experiment started to test seedlings' morphological response and capacity of recovery to ungulate browsing (Kupferschmid & Heiri, 2019) (Fig. 1B and C).…”
Section: Experimental Design and Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Review in Kupferschmid 2017). Weisstannen aus Hochlagenprovenienzen reagierten zum Beispiel zeitlich verzögert auf Triebschnitt (simulierter Verbiss), die Fichte hingegen nicht (Kupferschmid & Heiri 2019). Wildlebende Huftiere beeinflussen deshalb das Wachstum der Baumverjüngung je nach Baumart unterschiedlich, was deren relative Häufigkeit und damit deren Etablierungserfolg verändern kann (Krueger et al 2009).…”
unclassified